Differential diagnosis of vertigo and dizziness in the emergency department. (February 2014) - Ozono, Yoshiyuki; Kitahara, Tadashi; Fukushima, Munehisa; Michiba, Takahiro; Imai, Ryusuke; Tomiyama, Youichirou; Nishiike, Suetaka; Inohara, Hidenori; Morita, Hisaki
Abstract Conclusions: To establish a system of differential diagnosis for vertigo/dizziness at the Emergency Department (ED), careful history-taking of complications and examinations of nystagmus should be helpful and therefore prepared by ED staff. Objectives: Vertigo/dizziness could come from various kinds of organs for equilibrium, sometimes resulting in an emergency due to the central origin. In the present study, we checked patients' background data at the ED in advance of a definitive diagnosis at the Department of Otolaryngology and examined the significance of the correlation between the data and the diagnosis. Methods: We studied a series of 120 patients with vertigo/dizziness, who visited the Departments of Emergency and Otolaryngology between April 2011 and March 2012. At the ED, we first checked patients' backgrounds and carried out neurologic and neuro-otologic examinations. At the Department of Otolaryngology, we finally diagnosed all the patients according to the criteria and classified the origins of vertigo/dizziness into central and non-central diseases. Results: The ratio of patients with disease of central origin was 12.5% and that for non-central origin was 87.5%. The risk factors for cerebrovascular disease such as hypertension, heart disease, and diabetes were also the risk factors for central vertigo/dizziness by the chi-squared test. To predict a central origin for vertigo/dizziness, only gaze nystagmus was the significant factor by multivariate regression analysis.